Enabling hand-crafted visual markers at scale - Preston, William; Benford, Steve; Thorn, Emily-Clare; Koleva, Boriana; Rennick-Egglestone, Stefan; Mortier, Richard; Quinn, Anthony; Stell, John; Worboys, Michael (2017)
As locative media and augmented reality spread into the everyday world so it becomes important to create aesthetic visual markers at scale. We explore a designer-centred approach in which skilled designers handcraft seed designs that are automatically recombined to create many markers as subtle variants of a common theme. First, we extend the d-touch topological approach to creating visual markers that has previously been shown to support creative design with two new techniques: area order codes and visual checksums. We then show how the topological structure of such markers provides the basis for recombining designs to generate many variations. We demonstrate our approach through the creation of beautiful, personalized and interactive wallpaper. We reflect on how technologies must enable designers to balance goals of scalability, aesthetics and reliability in creating beautiful interactive decoration.